Complete Genome Sequences of Yersinia pestis from Natural Foci in China - Shen, Xiaona (American Society for Microbiology (ASM), 2010)
Yersinia pestis, the causative agent of plague, is a deadly bacterium that affects humans. Strain D106004 was isolated from a new plague focus in Yulong County, China, in 2006. To gain insights into the epidemic origin, we have sequenced the genomes of D106004 and strains Z176003 and D182038, isolated from neighboring regions.